Organic crop breeding - Lammerts van Bueren, E. T. [ (Edith T.)]; Myers, James Robert (Wiley-Blackwell, 2012)
Organic crop breeding provides readers with a thorough review of the latest efforts by crop breeders and geneticists to develop improved varieties for organic production